Posyandu cadres: their roles for improving health services in Jembayan Dalam Village - Febriyanto, Kresna; Wijaya, Ary Tri; Melda, Ranti; Ramadani, Rika; Utari, Rieke Chandra (Jurnal Kesehatan Ibu dan Anak, 2019)
Posyandu (Integrated Service Post) is a center of community activities where the community can simultaneously obtain family planning and health services including nutrition, immunization, Maternal and Child Health (MCH), and diarrhea prevention. Posyandu services are greatly supported by the role of cadres. Therefore, the role of cadres is needed to accelerate the reduction in maternal and infant mortality rates. The purpose of conducting this research is to find the role of posyandu cadres in health posyandu services. This study was qualitative research. Research respondents are informants were divided into two, namely the main informant consisting of 6 informants (as posyandu cadres) and 1 supporting informant (as health worker). Data collection techniques used by Focus Group Discussion. Posyandu cadres have implemented the principle of 5 tables when posyandu activities are taking place. In addition, the cadres also routinely attend training on the roles and duties of cadres in carrying out posyandu, so the cadres are able to provide basic health services, in order to accelerate the reduction in maternal and infant mortality rates. From the results of this study, it can be concluded that the implementation of the 6 aspects of the role of posyandu cadres has been well implemented in the Posyandu of Jembayan Village.